Educación ambiental para el manejo de los residuos sólidos en los barrios rurales de la ciudad de Loja El Carmen y Punzara Grande - Jara Guaman, Manuel Eduardo (2018)
Abstract:Environmental education has the fundamental purpose of educating and training citizens with principles and values of responsibility with the environment. Due to the current situation of rural neighborhoods: "El Carmen" and "Punzara Grande", for the inadequate management of their solid waste (SW), there is a need for design and run environmental education workshops, with the aim of contributing with strategies of solution to this problem. Previously, the current management of SRs was diagnosed, using direct field observation. Semi-structured interviews were applied to the neighborhood directives, and SWOT analyzes were carried out with their respective strategies. Also, a physical characterization of RS was carried out for each rural neighborhood. Seven samplings were carried out in different weeks, obtaining the following results: Punzara Grande neighborhood: greater percentage of organic waste with 37.76%, and in a lower percentage, hospital waste with 2.81%. El Carmen neifhborhood: highest percentage of organic waste with 33.59%, and the lowest percentage of hospital waste with 0.79%. Finally, with the villagers in participatory action, strategies and commitments were established to improve the management of SRs.